Evaluación de técnicas de plantación de Yerba Mate (Ilexparaguariensis S.H), cultivadas a campo en el municipio de Natalio, Paraguay (Journal on studies and research of academic knowledge, 2015)
This research was conducted in order to evaluate different planting techniques of yerba mate, aiming to develop a planting technology that allows greater survival of plants at field. The high mortality of plants at field level is one of the main problems that faces the producers, when installing a new crop of yerba mate. The plot installed in the campus of UNI in the district of Natalio remains as a pure cultive of yerba mate, to serve as study material for teachers and students of the institution. This research enabled students in thesis level, to conduct research in a relevant topic to the productive sector, being able to find a solution to problems that affect the producers with lower technical and economic capacities, that sees the yerba mate as a profitable alternative to generate income, which would result in a better life quality in the countryside.
Keywords: yerba mate; planting; survival